Combined Effects of Multiple Stressors: New Insights Into the Influence of Timing and Sequence - Brooks, Paul R.; Crowe, Tasman P. (Frontiers in Ecology and Evolution, 2019)
Complex regimes of stress arise when multiple stressors combine simultaneously, with varying degrees of temporal separation or variation in their sequential order. A manipulative field experiment was run to test whether doses of two stressors (Copper & Biocide) varied in their effects on marine epifauna and ecosystem functioning depending on their sequence, timing and delay before sampling. Our key finding was that time-lags between stressors led to longer-lasting effects. We also found that the sequential order of two stressors influenced effects on measures of ecosystem-level processes: for community respiration (CR) the metal-first sequence of stressors had a negative effect; for clearance rates the biocide-first sequence had the greater effect. Effects of stressors delivered simultaneously on CR and clearance rates were short-lived. Intra-individual effects on cellular viability did not correspond with effects on ecosystem-level variables. Results show that current frameworks for understanding and managing the effects of multiple stressors can be improved by incorporating temporal variation in both cause and effect.